Composite solid electrolyte membrane, preparation method thereof and solid-state battery
In the preparation of composite solid electrolyte membranes of solid state batteries, the laminated structure and pressing treatment are used to solve the problems of interface internal resistance and decomposition in traditional processes, the stability and conductivity of the battery are improved, and more efficient electrolyte membrane performance is achieved.
Patent Information
- Application Number
- CN202411438489.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
The preparation process of traditional composite solid electrolyte membranes has problems such as increased interface internal resistance, decomposition of sulfide solid electrolytes and uneven thickness control, resulting in limited battery performance and stability.
The composite solid electrolyte membrane is prepared by spraying sulfide solid electrolyte raw materials on the first substrate layer, and layering the second substrate layer on the surface, and then spraying halide solid electrolyte powder. After pressing, the composite solid electrolyte membrane is prepared. The second substrate is The layer isolates the air to prevent the decomposition of the sulfide solid electrolyte and improves the interface contact problem.
It improves the cycling stability and ionic conductivity of solid-state batteries, reduces the internal resistance of the battery, and enhances the mechanical strength and consistency of the electrolyte membrane.
Smart Images

Figure CN119297382A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a composite solid electrolyte membrane and a preparation method thereof, and a solid-state battery. Background Art
[0002] Solid-state batteries are energy storage elements that can store electrical energy and release it when needed. Compared with traditional liquid batteries, solid-state batteries use solid electrolytes instead of liquid or gel electrolytes for ion transmission, and have higher safety, higher energy density, faster charging speed and longer cycle life.
[0003] Solid-state electrolytes, as the medium for ion transmission in batteries, directly affect the performance and stability of solid-state batteries. Selecting suitable solid-state electrolytes is crucial for designing high-performance and high-stability solid-state batteries.
[0004] Halide solid electrolytes and sulfide solid electrolytes are the two solid electrolytes with the highest ionic conductivity discovered so far. The composite solid electrolyte membrane prepared by them has attracted widespread attention because it has the advantages of both halide solid electrolytes and sulfide solid electrolytes. However, there are still some problems in the preparation process of traditional composite solid electrolyte membranes. The traditional preparation process generally prepares the halide solid electrolyte layer and the sulfide solid electrolyte layer separately, and then stacks and composites them. The composite solid electrolyte membrane prepared by this process has the following problems: on the one hand, there is an interface between the halide solid electrolyte membrane and the sulfide solid electrolyte membrane, which increases the internal resistance of the battery. On the other hand, the sulfide solid electrolyte membrane is easy to decompose and produce harmful gases. Moreover, the thickness control of the electrolyte membrane prepared separately is uneven, the porosity fluctuates greatly, and the consistency is difficult to ensure. Summary of the invention
[0005] Based on this, it is necessary to provide a method that can avoid the problem of solid electrolyte falling off in the solid electrolyte membrane, and provide a composite solid electrolyte membrane and a preparation method thereof, and a solid-state battery.
[0006] In a first aspect, the present application provides a method for preparing a composite solid electrolyte membrane, comprising the following steps:
[0007] Spraying a sulfide solid electrolyte raw material on one side surface of the first substrate layer to prepare an electrolyte membrane precursor;
[0008] A second substrate layer is stacked on the surface of the first substrate layer on which the sulfide solid electrolyte is sprayed, and a halide solid electrolyte powder is sprayed on the surface of the second substrate layer on a side away from the first substrate layer to prepare an electrolyte membrane intermediate;
[0009] Pressing the electrolyte membrane intermediate to prepare a composite solid electrolyte membrane;
[0010] Wherein, both the first substrate layer and the second substrate layer are porous structures.
[0011] In some embodiments, the porosity of the first substrate layer is less than the porosity of the second substrate layer;
[0012] In some embodiments, the porosity of the first substrate layer is 50% to 85%.
[0013] In some embodiments, the porosity of the second substrate layer is 70% to 95%.
[0014] In some embodiments, the step of spraying the sulfide solid electrolyte raw material on one side surface of the first substrate layer includes: mixing the initial sulfide solid electrolyte with a binder and performing fiberization to prepare the sulfide solid electrolyte raw material;
[0015] In some embodiments, the initial sulfide solid electrolyte and the binder are mixed at a mass ratio of 95:5 to 99.9:0.1.
[0016] In some embodiments, the step of spraying the halide solid electrolyte comprises: spraying the halide solid electrolyte at every 1 cm 2 Spraying 0.1 mg to 500 mg of halide solid electrolyte powder on the surface of the second substrate layer;
[0017] In some embodiments, the halide solid electrolyte is sprayed once or more times.
[0018] In some embodiments, the step of spraying the halide solid electrolyte includes: vibrating the electrolyte membrane intermediate;
[0019] In some embodiments, the number of oscillating the electrolyte membrane intermediate is 1 or more times;
[0020] In some embodiments, the step of oscillating the electrolyte membrane intermediate specifically comprises: oscillating the electrolyte membrane precursor using a vibrating screen;
[0021] In some embodiments, the oscillation frequency of the vibrating screen is 20kHz~1000kHz.
[0022] In some embodiments, the step of spraying the halide solid electrolyte or the step of oscillating the electrolyte membrane intermediate is repeated one or more times.
[0023] In some embodiments, in the step of stacking the second substrate layer on the surface of one side of the first substrate layer sprayed with the sulfide solid electrolyte, the thickness ratio of the second substrate layer to the first substrate layer is 85:15 to 60:40.
[0024] In some embodiments, in the step of pressing the electrolyte membrane intermediate, the pressure of the pressing treatment is 2t~3t; the time of the pressing treatment is 0.5min~20min;
[0025] In some embodiments, the temperature of the pressing treatment is 60°C to 120°C;
[0026] In some embodiments, a compressive force is applied to a surface of the second substrate layer on which the halide solid electrolyte powder is sprayed;
[0027] In some embodiments, the pressing process is performed once.
[0028] In a second aspect, the present application further provides a composite solid electrolyte membrane, which is prepared by the above-mentioned composite solid electrolyte membrane preparation method.
[0029] In a third aspect, the present application also provides a solid-state battery, which includes a positive electrode sheet, a negative electrode sheet and the composite solid-state electrolyte membrane.
[0030] In the preparation method of the composite solid electrolyte membrane, a sulfide solid electrolyte is first sprayed on the first substrate layer, and then a second substrate layer is formed on the sulfide solid electrolyte, and then a halide solid electrolyte is sprayed on the second substrate layer, and then pressed. In this way, on the one hand, the second substrate layer can isolate the contact between the air and the sulfide solid electrolyte, prevent the decomposition of the sulfide solid electrolyte, and improve the cycle stability when applied to the battery. On the other hand, the second substrate layer is formed on the sulfide solid electrolyte, that is, the sulfide solid electrolyte is located between the first substrate layer and the second substrate layer. When pressed, under the action of pressure, the sulfide solid electrolyte will enter the first substrate layer and the second substrate layer respectively, improving the interface contact problem between the halide solid electrolyte layer and the sulfide solid electrolyte layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] FIG. 1 is a schematic diagram of a method for preparing a composite solid electrolyte membrane according to an embodiment. DETAILED DESCRIPTION
[0032] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0033] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0034] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0035] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0036] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0037] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0038] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.
[0039] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0040] As shown in FIG. 1 , a method for preparing a composite solid electrolyte membrane includes the following steps S11 to S13 .
[0041] S11, spraying a sulfide solid electrolyte raw material on one surface of the first substrate layer to prepare an electrolyte membrane precursor.
[0042] Exemplarily, the first substrate layer includes at least one of aramid, non-woven fabric, and PI (Polyimide).
[0043] Exemplarily, the sulfide solid electrolyte includes Li3PS4, aLi2S·(1-a)P2S5, 0<a<1, LGPS and Li6PS5X 12 At least one of, wherein X is Cl, Br or I.
[0044] Exemplarily, spraying the sulfide solid electrolyte raw material may be performed by a powder spraying device.
[0045] S12, stacking a second substrate layer on the surface of the first substrate layer sprayed with the sulfide solid electrolyte, and spraying a halide solid electrolyte powder on the surface of the second substrate layer away from the first substrate layer, to prepare an electrolyte membrane intermediate. The first substrate layer and the second substrate layer are both porous structures.
[0046] Exemplarily, spraying of the halide solid electrolyte raw material may be performed by a powder spraying device.
[0047] Exemplarily, the material of the second substrate layer includes at least one of aramid, non-woven fabric, and PI.
[0048] For example, the second substrate layer can be deposited on the first substrate layer by fiber deposition. The fiber deposition method includes but is not limited to sol-gel method, spin coating method, chemical vapor deposition or magnetic suspension deposition method, etc. The thickness and density of the second substrate layer can be controlled within a reasonable range by the fiber deposition process.
[0049] For example, the specific composition of the halide solid electrolyte is not limited in the present application. Optionally, the halide solid electrolyte may be Li a M b X6, wherein 1<a<5, M includes one or more metals, and X includes halogen elements such as Cl, Br, I, etc. Optionally, the halide solid electrolyte can be Li2ZrCl6, Li3InCl6, Li3YCl6, Li3ScCl6 and Li2HfCl6. The halide solid electrolyte has high ionic conductivity and low crystallinity, which helps to inhibit the dendrite growth of active materials such as metallic lithium, thereby improving the safety and cycle life of the solid-state battery.
[0050] S13, pressing the electrolyte membrane intermediate to prepare a composite solid electrolyte membrane.
[0051] In the preparation method of the composite solid electrolyte membrane, a sulfide solid electrolyte is first sprayed on the first substrate layer, and then a second substrate layer is formed on the sulfide solid electrolyte, and then a halide solid electrolyte is sprayed on the second substrate layer, and then pressed. In this way, on the one hand, the second substrate layer can isolate the contact between the air and the sulfide solid electrolyte, prevent the decomposition of the sulfide solid electrolyte, and improve the cycle stability when applied to the battery. On the other hand, the second substrate layer is formed on the sulfide solid electrolyte, that is, the sulfide solid electrolyte is located between the first substrate layer and the second substrate layer. When pressed, under the action of pressure, the sulfide solid electrolyte will enter the first substrate layer and the second substrate layer respectively, improving the interface contact problem between the halide solid electrolyte layer and the sulfide solid electrolyte layer.
[0052] Illustratively, the stability of sulfide solid electrolytes to lithium is higher than that of halide solid electrolytes, and the chemical stability of the solid electrolyte membrane can be improved by contacting the sulfide solid electrolyte with the lithium negative electrode.
[0053] In some embodiments, the porosity of the first substrate layer is less than the porosity of the second substrate layer. That is, the density of the first substrate layer is greater than that of the second substrate layer, and the dense first substrate layer can block the sulfide solid electrolyte, preventing the sulfide solid electrolyte from escaping from the first substrate layer, resulting in a decrease in lithium ion conductivity, especially in preventing the sulfide solid electrolyte from escaping during the pressing process. The second substrate layer has a larger porosity, which can increase the amount of sulfide solid electrolyte entering the second substrate layer, shorten the distance with the halide solid electrolyte, facilitate the formation of an ion transmission channel, and improve ion conductivity.
[0054] Further, the porosity of the first substrate layer is 50% to 85%. Exemplarily, the porosity of the first substrate layer may be, but is not limited to, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, etc. Further, the porosity of the second substrate layer is 70% to 95%. Exemplarily, the porosity of the second substrate layer may be, but is not limited to, 70%, 75%, 80%, 85%, 90% or 95%, etc. Within the above porosity range, an appropriate amount of sulfide solid electrolyte and / or halide solid electrolyte can be accommodated, with good ion passing ability, and mechanical strength is maintained.
[0055] In some embodiments, the step of spraying the sulfide solid electrolyte raw material on one side surface of the first substrate layer includes: mixing the initial sulfide solid electrolyte with a binder and performing fiberization to prepare the sulfide solid electrolyte raw material.
[0056] Exemplarily, the binder includes a fibrillated binder, which is transformed from a granular state to a fibrous state under the action of a high shear force. In this way, the binder can increase the bonding strength between the halide solid electrolyte and the first substrate layer, and further prevent the halide solid electrolyte from escaping from the first substrate layer.
[0057] In some embodiments, the fiberizable binder includes one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene (PE), and polypropylene (PP).
[0058] For example, fiberization can be performed by grinding or the like.
[0059] In some embodiments, the initial sulfide solid electrolyte and the binder are mixed at a mass ratio of 95:5 to 99.9:0.1. For example, the mass ratio of the initial sulfide solid electrolyte to the binder may be, but is not limited to, 95:5, 96:4, 97:3, 98:2, 99:1, 99.5:0.5 or 99.9:0.1, etc. In this way, the amount of sulfide solid electrolyte in the composite solid electrolyte can be ensured.
[0060] In some embodiments, the step of spraying the halide solid electrolyte includes: spraying the halide solid electrolyte at every 1 cm 2 0.1 mg to 500 mg of halide solid electrolyte powder is sprayed on the surface of the second substrate layer. 2 The mass of the halide solid electrolyte powder sprayed on the surface of the second substrate layer can be, but is not limited to, 0.1 mg, 0.5 mg, 1 mg, 5 mg, 10 mg, 50 mg, 100 mg, 150 mg, 200 mg, 250 mg, 300 mg, 350 mg, 400 mg, 450 mg or 500 mg. Further, per 1 cm 2 The mass of the halide solid electrolyte powder sprayed on the surface of the second substrate layer can be 50mg to 300mg. Within the above range, the amount of the halide solid electrolyte in the composite solid electrolyte can be within a suitable range to form a complete lithium ion transmission channel.
[0061] In some embodiments, the number of times the halide solid electrolyte is sprayed is 1 or more times. For example, the number of times the halide solid electrolyte is sprayed may be, but is not limited to, 1, 2, 3, 4, or 5 times. In this way, a halide solid electrolyte layer of suitable thickness can be formed on the second substrate layer.
[0062] In some embodiments, the step of spraying the halide solid electrolyte includes: oscillating the electrolyte membrane intermediate. When the sulfide solid electrolyte and the halide solid electrolyte are formed on the second substrate layer, especially in the form of powder, the pores between the powders can be reduced by oscillation, and the contact effect and connection strength between the powders can be improved during pressing.
[0063] In some embodiments, the number of times the electrolyte membrane intermediate is oscillated is 1 or more times. Exemplarily, the number of times the electrolyte membrane intermediate is oscillated may be, but is not limited to, 1, 2, 3, 4, or 5 times. In this way, the contact between the halide solid electrolytes and the sulfide solid electrolytes can be improved.
[0064] In some embodiments, the step of shaking the electrolyte membrane intermediate specifically includes: shaking the electrolyte membrane precursor using a shaker. Exemplarily, the shaker method can be performed by placing the electrolyte membrane intermediate in a shaker.
[0065] In some embodiments, the oscillation frequency of the vibrating screen is 20kHz to 1000kHz. Exemplarily, the oscillation frequency of the vibrating screen can be, but is not limited to, 20kHz, 50kHz, 80kHz, 100kHz, 150kHz, 200kHz, 250kHz, 300kHz, 350kHz, 400kHz, 450kHz, 500kHz, 550kHz, 600kHz, 650kHz, 700kHz, 750kHz, 800kHz, 850kHz, 900kHz, 950kHz or 1000kHz, etc.
[0066] In some embodiments, the step of spraying the halide solid electrolyte or the step of oscillating the electrolyte membrane intermediate is repeated one or more times. For example, the number of times of spraying the halide solid electrolyte or the step of oscillating the electrolyte membrane intermediate can be, but is not limited to, one, two, three, four, or five times.
[0067] In some embodiments, in the step of stacking the second substrate layer on the surface of one side of the first substrate layer sprayed with the sulfide solid electrolyte, the thickness ratio of the second substrate layer to the first substrate layer is 85:15~60:40. Exemplarily, the thickness ratio of the second substrate layer to the first substrate layer can be, but is not limited to, 85:15, 85:20, 85:25, 85:30, 85:35, 85:40, 80:40, 75:40, 70:40, 65:40 or 60:40, etc. Within the above range, on the one hand, the thickness of the first substrate layer is less than that of the second substrate layer, which facilitates the sulfide to pass through the first substrate layer during pressing, thereby improving the contact effect with the electrode. On the other hand, the second substrate layer has a large thickness, which can partially isolate the sulfide solid electrolyte and the halide solid electrolyte, and optimize the interface problem between the halide solid electrolyte and the sulfide solid electrolyte.
[0068] In some embodiments, in the step of pressing the electrolyte membrane intermediate, the pressure of the pressing treatment is 2t~3t; the time of the pressing treatment is 0.5min~20min. For example, the pressure of the pressing treatment can be but not limited to 2t, 2.2t, 2.4t, 2.5t, 2.6t, 2.8t or 3t, etc. The time of the pressing treatment can be but not limited to 0.5min, 1min, 2min, 5min, 8min, 10min, 12min, 15min, 18min or 20min, etc. For example, the pressing method can be flat plate pressing or roller pressing.
[0069] In some embodiments, the temperature of the press treatment is 60° C. to 120° C. For example, the temperature of the press treatment may be, but is not limited to, 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., or 120° C.
[0070] In some embodiments, a pressing force is applied to the surface of the second substrate layer on the side where the halide solid electrolyte powder is sprayed. Exemplarily, these embodiments refer to unidirectional pressing, that is, the pressing side is the side sprayed with the halide solid electrolyte powder. In this way, the sulfide solid electrolyte is exposed from the first substrate layer.
[0071] In some embodiments, the pressing process is performed once. The composite solid electrolyte membrane can be obtained by pressing once, because the second substrate layer can block the sulfide solid electrolyte.
[0072] In some embodiments, a composite solid electrolyte membrane is also provided, which is prepared by the method for preparing the composite solid electrolyte membrane provided by any of the above embodiments.
[0073] In some embodiments, a solid-state battery is also provided, comprising a positive electrode sheet, a negative electrode sheet, and a composite solid electrolyte membrane prepared by the preparation method of the composite solid electrolyte membrane provided in any of the above embodiments. In some embodiments, the particle size of the sulfide solid electrolyte is 1 μm ~ 10 μm. Optionally, the particle size of the sulfide solid electrolyte can be but is not limited to 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. In this way, the sulfide solid electrolyte can be blocked by the second substrate layer to avoid passing through or destroying the pores of the first substrate layer from the second substrate layer. Preferably, the particle size of the sulfide solid electrolyte is 4 μm ~ 6 μm. Optionally, the above particle size is the value of particle size D50.
[0074] In some embodiments, the particle size of the halide solid electrolyte is 0.1 μm ~ 3 μm. Optionally, the particle size of the halide solid electrolyte can be but is not limited to 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm. In this way, the halide solid electrolyte can be accommodated in the second substrate layer and reduce the probability of escape without destroying the pores of the second substrate layer. Preferably, the particle size of the halide solid electrolyte is 1 μm ~ 2 μm. Optionally, the above particle size is the value of particle size D50.
[0075] Optionally, a solid-state battery, including an all-solid-state battery or a semi-solid-state battery.
[0076] Positive electrode:
[0077] In some embodiments, the secondary battery provided by the present invention includes a positive electrode, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer having a thickness of greater than or equal to about 1 μm to less than or equal to about 1,000 μm. The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a compound that reversibly intercalates and deintercalates lithium ions.
[0078] In some embodiments, the positive electrode active material comprises one or more transition metal cations, such as manganese (Mn), nickel (Ni), cobalt (Co), chromium (Cr), iron (Fe), vanadium (V), and combinations thereof.
[0079] In some embodiments, the positive electrode active material is one of a layered oxide, a spinel, and a polyanion. For example, the layered oxide (e.g., a rock salt layered oxide) comprises one or more lithium-based positive electrode active materials selected from the group consisting of LiCoO2 (LCO), LiNi x Mn y Co 1-x-y O2 (where 0≤x≤1 and 0≤y≤1), LiNi 1-x-y Co x Al y O2 (where 0≤x≤1 and 0≤y≤1), LiNi x Mn 1-x O2 (where 0≤x≤1), and Li 1+x MO2 (wherein M is one of Mn, Ni, Co and Al and 0≤x≤1). The spinel comprises one or more lithium-based positive active materials selected from the group consisting of LiMn2O4 (LMO) and LiNi x Mn 1.5O4. The olivine type contains one or more lithium-based positive electrode active materials LiMPO4 (wherein M is at least one of Fe, Ni, Co and Mn). The polyanion cation contains, for example, phosphates such as LiV2(PO4)3 and / or silicates such as LiFeSiO4.
[0080] In some embodiments, the positive electrode active material layer includes a binder, which improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material layer and the positive electrode current collector.
[0081] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0082] In some embodiments of the present invention, the mass of the binder accounts for 1%-20% of the mass of the positive electrode material layer.
[0083] In some embodiments of the present invention, the positive electrode active material layer includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0084] In some embodiments, the mass of the conductive agent accounts for 1%-20% of the mass of the positive electrode material layer.
[0085] In some embodiments, the positive electrode plate provided by the present invention further includes a fast ion conductor for improving the ionic conductivity of the positive electrode. The present invention does not limit the type of fast ion conductor, which can be an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a lithium salt, etc. Optionally, the mass of the fast ion conductor accounts for 1%-20% of the mass of the positive electrode plate; preferably 5%-20%.
[0086] In some embodiments, the positive electrode sheet includes a positive electrode current collector. Exemplarily, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0087] It is understood that the above examples of positive electrode active materials, binders, and conductive materials are only illustrative, and any known positive electrode active materials, binders, and conductive materials can be used in this application without violating the inventive concept of this application. And the addition of known additives based on actual use requirements should also be considered within the scope of protection of this application.
[0088] Negative electrode:
[0089] In some embodiments of the present invention, the negative electrode sheet includes a current collector and a negative electrode active material layer disposed on the current collector.
[0090] In the present invention, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel-structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0091] In some embodiments, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0092] In some embodiments, the mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80%-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.
[0093] In some embodiments, the negative electrode material layer may include a binder; the binder improves bonding of negative electrode active material particles to each other and bonding of the negative electrode active material to the current collector.
[0094] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, and the like.
[0095] In some embodiments, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.
[0096] In some embodiments, the aforementioned viscosity enhancer may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.
[0097] In some embodiments, the mass proportion of the thickener in the negative electrode slurry can be 0.1%-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%-3%, and more preferably 0.6%-2%.
[0098] In some embodiments, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0099] In some embodiments of the present invention, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0100] Secondary battery:
[0101] In some embodiments, the secondary battery of the present invention comprises the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto.
[0102] In some embodiments, the secondary battery according to the present invention is made by stacking the above-mentioned positive and negative electrode sheets.
[0103] In some embodiments, the secondary battery of the present invention may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0104] The following are specific embodiments.
[0105] Example 1
[0106] Preparation of composite solid electrolyte membrane:
[0107] (1) Spraying a sulfide solid electrolyte raw material on one side surface of the first substrate layer to prepare an electrolyte membrane precursor; the sulfide solid electrolyte raw material includes a sulfide solid electrolyte Li6PS5Cl and a binder PTFE, and the mass ratio of the two is 99:1; Li6PS5Cl 12 The particle size D50 is 1.8 μm, and the sulfide solid electrolyte Li6PS5Cl 12 and the binder PTFE are put into a mixer for fiberization treatment to form a sulfide solid electrolyte raw material; the first substrate layer is a non-woven fabric, the porosity of the first substrate layer is 70%; the thickness of the first substrate layer is 5 μm.
[0108] (2) A second substrate layer is stacked on the surface of the first substrate layer on which the sulfide solid electrolyte is sprayed, and a halide solid electrolyte powder is sprayed on the surface of the second substrate layer away from the first substrate layer to prepare an electrolyte membrane intermediate.
[0109] The second substrate layer completely covers the area of the first substrate layer where the sulfide solid electrolyte powder is sprayed.
[0110] The second substrate layer is a nonwoven fabric with a porosity of 85% and a thickness of 15 μm.
[0111] The halide solid electrolyte raw materials include the halide solid electrolyte Li3InCl6 and the binder PTFE, the mass ratio of the two is 99:1; the particle size D50 of Li3InCl6 is 5μm; 2 300 mg of halide solid electrolyte powder is sprayed on the surface of the second substrate layer.
[0112] (3) The electrolyte membrane intermediate is vibrated by using a vibrating screen, and the oscillation frequency of the vibrating screen is 300 kHz.
[0113] (4) Repeat steps (2) to (3) three times.
[0114] (5) The electrolyte membrane intermediate is pressed to prepare a composite solid electrolyte membrane.
[0115] The pressure of the pressing treatment is 2t; the time of the pressing treatment is 10min; the temperature of the pressing treatment is 60°C; and the pressing force is applied to the surface of one side of the second substrate layer sprayed with the halide solid electrolyte powder.
[0116] The pressing number of the pressing process was 1.
[0117] Preparation of lithium-ion batteries:
[0118] The positive electrode sheets are aligned and stacked on one side of the first substrate layer in the composite solid electrolyte membrane, and after rolling, the negative electrode sheets are attached to the second substrate layer in the solid electrolyte membrane, and assembled with the shell to obtain a button-type lithium-ion battery. The positive electrode composition is 95wt% NCM622, 3wt% PTFE and 2wt% super-P; the negative electrode is Li-In alloy.
[0119] Example 2
[0120] The preparation method of Example 2 is substantially the same as that of Example 1, except that:
[0121] In step (1), the porosity of the first substrate layer is 50%;
[0122] In step (2), the porosity of the second substrate layer is 70%.
[0123] Example 3
[0124] The preparation method of Example 3 is substantially the same as that of Example 1, except that:
[0125] In step (1), the porosity of the first substrate layer is 85%;
[0126] In step (2), the porosity of the second substrate layer is 95%.
[0127] Example 4
[0128] The preparation method of Example 4 is substantially the same as that of Example 1, except that:
[0129] In step (1), the porosity of the first substrate layer is 75%;
[0130] In step (2), the porosity of the second substrate layer is 75%.
[0131] Example 5
[0132] The preparation method of Example 5 is substantially the same as that of Example 1, except that:
[0133] In step (1), the thickness of the first substrate layer is 6 μm;
[0134] In step (2), the thickness of the second substrate layer is 34 μm.
[0135] Example 6
[0136] The preparation method of Example 6 is substantially the same as that of Example 1, except that:
[0137] In step (1), the thickness of the first substrate layer is 8 μm;
[0138] In step (2), the thickness of the second substrate layer is 12 μm.
[0139] Example 7
[0140] The preparation method of Example 7 is substantially the same as that of Example 1, except that:
[0141] In step (5), the pressure of the pressing treatment is 3t; and the time of the pressing treatment is 5min.
[0142] Example 8
[0143] The preparation method of Example 8 is substantially the same as that of Example 1, except that:
[0144] In step (2), at every 1 cm 2 500 mg of halide solid electrolyte powder is sprayed on the surface of the second substrate layer.
[0145] Example 9
[0146] The preparation method of Example 9 is substantially the same as that of Example 1, except that:
[0147] In step (1), the particle size D50 of Li6PS5Cl is 3 μm.
[0148] Example 10
[0149] The preparation method of Example 10 is substantially the same as that of Example 1, except that:
[0150] In step (1), the sulfide solid electrolyte is Li 10 GeP2S 12 ;
[0151] In step (2), the halide solid electrolyte is Li2ZrCl6.
[0152] Comparative Example 1
[0153] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that: Preparation of the solid electrolyte membrane:
[0154] (1) spraying a sulfide solid electrolyte raw material on one side surface of the first substrate layer and pressing to form a sulfide solid electrolyte layer;
[0155] (2) spraying a halide solid electrolyte raw material on one surface of the second substrate layer and pressing to form a halide solid electrolyte layer;
[0156] (3) The sulfide solid electrolyte layer and the halide solid electrolyte layer are stacked and pressed to form a solid electrolyte membrane.
[0157] The process parameters of Examples 1 to 10 and Comparative Example 1 are listed in Table 1. Among them: the porosity is tested by using an SSA-4200 pore size and specific surface area analyzer, and the solid electrolyte particle size is tested by using a Malvern dry particle size analyzer.
[0158] Table 1
[0159]
[0160] The test results are shown in Table 2 below, where the test conditions or test standards for each performance test item are:
[0161] (1) Ionic conductivity test
[0162] At 25°C, the test structure of stainless steel sheet / solid electrolyte membrane / stainless steel sheet was used, the frequency range was 0.1Hz-7MHz, and the AC signal amplitude Z was 10 -2 The AC impedance test was carried out under the condition of V, and the ionic conductivity was calculated according to the formula σ=L / (S*R), where L is the thickness of the solid electrolyte membrane, S is the cross-sectional area of the solid electrolyte membrane, and R represents the charge transfer resistance.
[0163] (2) Cyclic performance test
[0164] At a temperature of 25℃±2℃, in the first step, charge at 0.1C or specified current to the termination voltage, with a cutoff current of 0.01C, and let stand for 30 minutes; in the second step, discharge at 0.1C to the discharge final voltage (2.75V), record the discharge capacity, and let stand for 30 minutes; cycle the first and second steps to test the cycle performance of the lithium-ion battery for 300 cycles.
[0165] Table 2
[0166]
[0167] It can be seen from Table 2 above that by comparing Examples 1 to 10 and Comparative Example 1, the composite solid electrolyte membrane prepared by the method for preparing a composite solid electrolyte membrane provided by the present application has good ionic conductivity, and after the secondary battery is prepared, it can provide a good cycle capacity retention rate, that is, cycle stability, and effectively reduce the internal resistance of the battery.
[0168] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0169] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A method for preparing a composite solid electrolyte membrane, characterized in that: The following steps are involved: Spraying a sulfide solid electrolyte raw material on one side surface of the first substrate layer to prepare an electrolyte membrane precursor; A second substrate layer is stacked on the surface of the first substrate layer on which the sulfide solid electrolyte is sprayed, and a halide solid electrolyte powder is sprayed on the surface of the second substrate layer on a side away from the first substrate layer to prepare an electrolyte membrane intermediate; Pressing the electrolyte membrane intermediate to prepare a composite solid electrolyte membrane; Wherein, both the first substrate layer and the second substrate layer are porous structures.
2. The preparation method according to claim 1, characterized in that: The porosity of the first substrate layer is less than the porosity of the second substrate layer; Preferably, the porosity of the first substrate layer is 50% to 85%; Preferably, the porosity of the second substrate layer is 70% to 95%.
3. The preparation method according to claim 1, characterized in that: The step of spraying the sulfide solid electrolyte raw material on one side surface of the first substrate layer comprises: mixing the initial sulfide solid electrolyte with a binder and performing fiberization to prepare the sulfide solid electrolyte raw material; Preferably, the initial sulfide solid electrolyte and the binder are mixed in a mass ratio of 95:5 to 99.9:0.
1.
4. The preparation method according to claim 1, characterized in that: The step of spraying the halide solid electrolyte comprises: spraying the halide solid electrolyte at every 1 cm 2 Spraying 0.1 mg to 500 mg of halide solid electrolyte powder on the surface of the second substrate layer; Preferably, the halide solid electrolyte is sprayed once or more times.
5. The preparation method according to claim 1, characterized in that: The step of spraying the halide solid electrolyte includes: vibrating the electrolyte membrane intermediate; Preferably, the number of oscillating the electrolyte membrane intermediate is 1 time or more; Preferably, the step of oscillating the electrolyte membrane intermediate specifically comprises: oscillating the electrolyte membrane precursor using a vibrating screen; Preferably, the oscillation frequency of the vibrating screen is 20kHz~1000kHz.
6. The preparation method according to claim 4 or 5, characterized in that: The step of spraying the halide solid electrolyte or the step of oscillating the electrolyte membrane intermediate is repeated one or more times.
7. The preparation method according to claim 1, characterized in that: In the step of laminating the second substrate layer on the surface of one side of the first substrate layer sprayed with the sulfide solid electrolyte, the thickness ratio of the second substrate layer to the first substrate layer is 85:15-60:
40.
8. The preparation method according to claim 1, characterized in that: In the step of pressing the electrolyte membrane intermediate, the pressure of the pressing treatment is 2t~3t; the time of the pressing treatment is 0.5min~20min; Preferably, the temperature of the pressing treatment is 60°C to 120°C; Preferably, a compressive force is applied to the surface of the second substrate layer on one side of which the halide solid electrolyte powder is sprayed; Preferably, the pressing process is performed once.
9. A composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane is prepared by the preparation method according to any one of claims 1 to 8.
10. A solid-state battery, characterized in that: The solid-state battery comprises a positive electrode sheet, a negative electrode sheet and the composite solid electrolyte membrane according to claim 9.
Citation Information
Cited By
Solid-state battery cell and preparation method therefor, battery device and electric device
WO2026166273A1